2014
DOI: 10.1186/1471-2164-15-369
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor gene family in the Pacific oyster, Crassostrea gigas, contains a novel subfamily group

Abstract: BackgroundNuclear receptors are a superfamily of transcription factors important in key biological, developmental and reproductive processes. Several of these receptors are ligand- activated and through their ability to bind endogenous and exogenous ligands, are potentially vulnerable to xenobiotics. Molluscs are key ecological species in defining aquatic and terrestrial habitats and are sensitive to xenobiotic compounds in the environment. However, the understanding of nuclear receptor presence, function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 150 publications
7
71
0
Order By: Relevance
“…3). This phylogenetic relationship between CgNR8A1 and other NR subfamilies was consistent with that observed in a previous study on NR genes in C. gigas (Vogeler et al, 2014). Indeed, NvNR8A1 was an outgroup of NR1/4 and not assigned to a known NR subfamily in a previous study focusing on NR genes in N. vectensis (Reitzel and Tarrant, 2009).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…3). This phylogenetic relationship between CgNR8A1 and other NR subfamilies was consistent with that observed in a previous study on NR genes in C. gigas (Vogeler et al, 2014). Indeed, NvNR8A1 was an outgroup of NR1/4 and not assigned to a known NR subfamily in a previous study focusing on NR genes in N. vectensis (Reitzel and Tarrant, 2009).…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, a recently published study on the NR genes in C. gigas reported that CgNHR42 (named as CgNR8A1 in this study) was an outgroup of NR2/3/5/6 and was described as a pseudogene (Vogeler et al, 2014). To investigate whether CgNR8A1 had any homologs in other animal species, an extensive BLASTp search was conducted against non-redundant protein sequences in NCBI.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There may be differences of inherent coregulators or carryover of non-genomic ER signaling elements of the later. Nuclear receptor (NR) mining from the genome of the Pacific oyster C. gigas has not clearly revealed the presence of NR3 members, which could interact with vertebrate sex steroids (Vogeler et al, 2014). This result provides increasing evidence that the steroid ligand specific expansion of this family is deuterostome specific (Vogeler et al, 2014).…”
Section: Debatable Studies Of Presence and Biological Functions Of Sementioning
confidence: 80%